The Meyah Marriage System in Manokwari, West Papua, as a Means of Preserving Local Culture and Aesthetics - Dowansiba, Yosias; Syufi, Yafet; Nauw, Monica M. (Journal of Aesthetics, Creativity and Art Management, 2025)
Marriage as a means of procreation and establishing kinship networks forms the basis of societal structures, with offspring ensuring continuity of lineage and social status. The traditional marriage system of the Meyah tribe in Manokwari Province, West Papua, Indonesia, is of interest to study to assess a process commonly practiced by the indigenous people. In this research, an ethnographic approach facilitates a comprehensive examination of cultural practices and rituals, as well as their aesthetics, yielding significant insights into the relevance of the Meyah community's marriage customs. The analysis reveals that the implementation of the marriage system is currently a challenge for the majority of the Meyah population, especially young men and women. The indigenous Meyah community still has a limited understanding of cultural values, such as marriage structure, normative framework, legal system, and specific regulations still applied in daily life. The decline in traditional leaders leading this traditional system has resulted in differences between the older and younger generations regarding the understanding and implementation of marriage customs. This requires initiatives aimed at educating and representing the importance of cultural and artistic values.